2014
DOI: 10.1371/journal.pone.0101568
|View full text |Cite
|
Sign up to set email alerts
|

Expertise in Musical Improvisation and Creativity: The Mediation of Idea Evaluation

Abstract: The current study explored the influence of musical expertise, and specifically training in improvisation on creativity, using the framework of the twofold model, according to which creativity involves a process of idea generation and idea evaluation. Based on the hypothesis that a strict evaluation phase may have an inhibiting effect over the generation phase, we predicted that training in improvisation may have a “releasing effect” on the evaluation system, leading to greater creativity. To examine this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 38 publications
(35 reference statements)
3
23
0
6
Order By: Relevance
“…Given that dedication of attentional resources to task unrelated stimuli reduces an individual's capacity for rational evaluation of an idea's creativity 12 , distractions may simultaneously have biasing effects on idea evaluation and positive effects on idea selection. Consistent with these recent findings, researchers have suggested that relaxing evaluation criteria may result in more creative outcomes 9,80 . The possibility that distractions may, should they reduce deliberative processing and improve intuitive processing, enhance creative idea selection is an interesting question for researchers interested in which ideas are eventually acted upon.…”
Section: Discussionmentioning
confidence: 54%
“…Given that dedication of attentional resources to task unrelated stimuli reduces an individual's capacity for rational evaluation of an idea's creativity 12 , distractions may simultaneously have biasing effects on idea evaluation and positive effects on idea selection. Consistent with these recent findings, researchers have suggested that relaxing evaluation criteria may result in more creative outcomes 9,80 . The possibility that distractions may, should they reduce deliberative processing and improve intuitive processing, enhance creative idea selection is an interesting question for researchers interested in which ideas are eventually acted upon.…”
Section: Discussionmentioning
confidence: 54%
“…Idea generation is the process of mentally combining or recombining existing elements to give rise to multiple possible solutions, whereas idea evaluation entails selecting from the array of generated ideas, using internally or externally generated feedback. Because feedback can come from multiple sources at different times during or after the performance, this feedforward/feedback cycle between idea generation and evaluation occurs at multiple timescales …”
Section: Conceptualizing the Real‐time Creative Musical Processmentioning
confidence: 99%
“…Because feedback can come from multiple sources at different times during or after the performance, this feedforward/feedback cycle between idea generation and evaluation occurs at multiple timescales. [10][11][12] At an implementational level, this interplay of idea generation and evaluation likely entails the coordinated activity of the default mode and executive control networks in the brain as detailed in the next section. 13 As ideas in improvised music are implemented as auditory-motor sequences, the perception and production of these sound targets further engages the auditory perception-action network, 14,15 which is strengthened in its connectivity by musical training.…”
Section: Conceptualizing the Real-time Creative Musical Processmentioning
confidence: 99%
“…This finding highlights the close link between improvisation, repetition and variation, and creative processes. Kleinmintz et al (2014) points out that musical improvisation increases creativity. The link between improvisation and creativity was also emphasized in neurobiology, where it was found that the greater connectivity between brain regions sharing functional properties observed in professional improvisers may be due to a more efficient working of the associative networks of musical creativity ( Pinho et al, 2014 ; see also Beaty, 2015 ).…”
Section: Discussionmentioning
confidence: 99%